2022
DOI: 10.21203/rs.3.rs-1988668/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isoflurane enhances autophagy by activating AMPK/ULK1, inhibits NLRP3, and reduces cognitive impairment after cerebral ischemia-reperfusion injury in rats

Abstract: Background Cerebral ischemia-reperfusion injury (CIRI) is an important factor affecting the prognosis of patients with ischemic stroke. This study aimed to observe whether isoflurane posttreatment enhances autophagy after focal CIRI in rats by activating the AMPK/ULK1 signaling pathway, thereby inhibiting NLRP3 inflammation. The body releases inflammatory factors to reduce inflammation, thereby reducing neurological damage and improving cognitive and memory functions. Methods Eighty male SD rats were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These pro‐inflammatory factors can cross the placenta and the immature fetal blood–brain barrier and reach the fetal brain, where they induce an inflammatory response after birth (Entringer et al., 2010; Zhao et al., 2015). A previous study found that isoflurane exposure downregulated the pro‐inflammatory factors (such as IL‐18 and IL‐1β) in rats suffering from cerebral ischemia–reperfusion injury, and improved neuroinflammation and cognitive function (Zhai et al., 2023). However, one study showed that IL‐6 was significantly upregulated in the brains of offspring mice exposed to sevoflurane for 3 h on GD15.5, and this was accompanied by learning impairment, as assessed in the Y ‐maze test (Hirotsu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These pro‐inflammatory factors can cross the placenta and the immature fetal blood–brain barrier and reach the fetal brain, where they induce an inflammatory response after birth (Entringer et al., 2010; Zhao et al., 2015). A previous study found that isoflurane exposure downregulated the pro‐inflammatory factors (such as IL‐18 and IL‐1β) in rats suffering from cerebral ischemia–reperfusion injury, and improved neuroinflammation and cognitive function (Zhai et al., 2023). However, one study showed that IL‐6 was significantly upregulated in the brains of offspring mice exposed to sevoflurane for 3 h on GD15.5, and this was accompanied by learning impairment, as assessed in the Y ‐maze test (Hirotsu et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…[69] Man Long et al observed that electroacupuncture pretreatment diminished TRPV1 expression, thereby inhibiting the NF-κβ pathway's transcriptional activity and exerting antiapoptotic effects. [70] Isoflurane [71] and the proprietary Chinese medicine Pien Tze Huang (PTH) [72] upregulate autophagy through activation of the AMPK/ULK1 pathway, thereby inhibiting the release of NLRP3 and inflammatory factors such as IL-1β and IL-18. Li Mao et al deduced that heightened Toll-like receptor 4 expression could induce CIRI by modulating NLRP3 inflammasome and autophagy, though the precise mechanism remains under investigation.…”
Section: Relationship Between Autophagy and Inflammation In Cirimentioning
confidence: 99%